2019
DOI: 10.1111/are.14064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietarydl‐methionyl‐dl‐methionine (Met‐Met) on growth performance, body composition and haematological parameters of white shrimp (Litopenaeus vannamei) fed with plant protein–based diets

Abstract: A 10‐week feeding trial was conducted to evaluate the effects of supplementing different levels of dl‐methionyl‐dl‐methionine (AQUAVI® Met‐Met) in plant protein–based diets on Litopenaeus vannamei. The positive control (PC) and negative control (NC) diets were designed with 20% and 8% fishmeal respectively, and other six diets were formulated with graded levels of Met‐Met from 0.05% to 0.30% with a 0.05% increment on the basis of NC diet (MM 0.05–MM 0.3). Six replicates were randomly assigned to each diet with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
3
8
0
Order By: Relevance
“…Moisture contents were not affected by dietary methionine levels, which were in agreement with other researches (Huang & Lin, 2002; Wang et al., 2019; Xie et al., 2018). It has been reported that both crude protein and crude lipid in carcass were affected significantly by dietary methionine levels, such as yellow tail Seriola quinqueradiata (Ruchimat et al., 1997), Indian catfish Heteropneustes fossilis (Ahmed, 2014), rainbow trout oncorhynchus mykiss (Alami‐Durante et al., 2018) and cobia Rachycentron canadum (Wang et al., 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moisture contents were not affected by dietary methionine levels, which were in agreement with other researches (Huang & Lin, 2002; Wang et al., 2019; Xie et al., 2018). It has been reported that both crude protein and crude lipid in carcass were affected significantly by dietary methionine levels, such as yellow tail Seriola quinqueradiata (Ruchimat et al., 1997), Indian catfish Heteropneustes fossilis (Ahmed, 2014), rainbow trout oncorhynchus mykiss (Alami‐Durante et al., 2018) and cobia Rachycentron canadum (Wang et al., 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Generally, dietary methionine can affect growth and lipid metabolism via GCN2 pathway (Wang et al., 2016) and increased the expression of IGF‐1(Espe et al., 2016; Shan et al., 2017). But there were no effects on crude protein and crude lipid content in carcass of softshell turtle Pelodiscus sinensis (Huang & Lin, 2002) and white shrimp Litopenaeus vannamei (Niu et al., 2018; Wang et al., 2019). This may be related to the experimental treatment, especially the dietary methionine levels, and may also be related to the experimental animal species.…”
Section: Discussionmentioning
confidence: 99%
“…Fishmeal (FM) is the major ingredient for aquaculture mainly due to its favourable amino acid and fatty acid profiles, palatable taste and high protein content, as well as unidentified growth factors for aquaculture species (Wang, Ye, et al, ). With the rapid growth of global aquaculture industry, FM demand has been increasing in recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with FM, CGM lacks of arginine and lysine, whereas PPI has comparable amino acid profile as shown in Table . Supplementation of indispensable amino acids (IAA) to alternative protein source is an effective way to obtain balanced amino acid profile (Gao et al, ; Wang, Ye, et al, ; Zhang, Øverland, Sørensen, et al, ), thus improving the nutritive value of plant protein and maximizing growth of fish (Gómez‐Requeni et al, ). Besides, studies have found that both CGM (Bu et al, ; Men et al, ) and PPI (Gao et al, ) have relatively good protein digestibility in different fish species.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have, however, been focused on fish. For instance, dietary Met supplements have been shown to improve growth performance in different fish species (144,(154)(155)(156)(157)(158). Specifically, lack of Met in feed could affect protein synthesis and reduce feed utilization in flatfish (Solea senegalensis) and white bass (Morone chrysops) (159,160), as well as induce general mitochondrial dysfunction in liver of rainbow trout (Oncorhynchus mykiss) (161).…”
Section: Methionine and Cysteinementioning
confidence: 99%